Resistance to the oat leaf blotch pathogen (Pyrenophora avenae) is delimited to a region of chromosome 1D that harbors a candidate resistance kinase fusion protein - Aaron D. Beattie; Peter E. Eckstein; Alex Woitas; Tajinder S. Grewal; Lindsay J. Griffith; Xiang M. Zhang; Nadia Kamal; Namratha Pavuluri; Curt McCartney (Theoretical and Applied Genetics, 2026)

Adherence to the Eatwell Guide and associations with markers of physical function: a prospective analysis within the UK Biobank cohort - Alex Griffiths; Sarah Gregory; Fiona C. Malcomson; Kirstie Cronin; Jamie Matu; Louisa Ells; Oliver M. Shannon (GeroScience, 2026)
The Eatwell Guide represents the UK’s principal healthy eating model and understanding whether adherence to UK dietary recommendations can attenuate age-related functional decline is essential to inform healthy ageing strategies. In up to 157,457 participants from the UK Biobank, we explored cross-sectional and prospective associations between adherence to the Eatwell Guide and markers of physical function (grip strength, fat-free mass percentage, self-reported walking pace, and falls). Eatwell Guide adherence scores were derived from 24-h dietary recall data (Oxford WebQ), and quantified using a graded, food-based scoring system. Differences between population subgroups including by age, sex, physical activity, and protein intake level were explored. Higher Eatwell Guide adherence was cross-sectionally associated with higher grip strength, greater fat-free mass percentage, higher odds of brisk walking pace, and lower odds of falls (all p < 0.001). Prospectively, greater adherence was associated with attenuated fat-free mass decline (β = 0.02, SE = 0.001, p < 0.001) and slower grip strength decline (β = 0.01, SE = 0.002, p < 0.01). For walking pace, the positive cross-sectional association attenuated over follow-up (EWG × time interaction OR = 0.998, 95% CI 0.997–0.999, p = 0.002), whereas the protective association with falls remained stable over time (OR = 1.000, 95% CI 0.998–1.000, p = 0.89). Higher Eatwell Guide adherence was associated with preserved muscle mass, modest attenuation of grip strength decline over time, and a reduced risk of falls, supporting its relevance for musculoskeletal health and physical function in aging populations.

Pathways and processes controlling the distribution of anthropogenic lead in the interior of the Southern Ocean - Alex Griffiths; Yee-Lap Leung; Andrew R. Bowie; Melanie East; Mark Rehkämper; Tina van de Flierdt (Geochimica et Cosmochimica Acta, 2026)

Biometal concentrations, distribution and re-distribution in the thymus of healthy mice and mice with inflammatory arthritis - Theoharris Frangos; Alex Griffiths; Alexander Morrell; Wolfgang Maret (Journal of Trace Elements in Medicine and Biology, 2025)

Effects of dietary nitrate supplementation on oral health and associated markers of systemic health: a systematic review - Shatha S. Alhulaefi; Anthony W. Watson; Sheena E. Ramsay; Nick S. Jakubovics; Jamie Matu; Alex Griffiths; Rachel Kimble; Mario Siervo; Kirsten Brandt; Oliver M. Shannon (Critical Reviews in Food Science and Nutrition, 2025)

Animal social networks are robust to changing association definitions - Alex Hoi Hang Chan; Jamie Dunning; Kristina B Beck; Terry Burke; Heung Ying Janet Chik; Daniel Dunleavy; Tim Evans; André Ferreira; Babette Fourie; Simon C. Griffith; Friederike Hillemann; Julia Schroeder (Behavioral Ecology and Sociobiology, 2025)
The interconnecting links between individuals in an animal social network are often defined by discrete, directed behaviours, but where these are difficult to observe, a network link (edge) may instead be defined by individuals sharing a space at the same time, which can then be used to infer a social association. The method by which these associations are defined should be informed by the biological significance of edges, and therefore often vary between studies. Identifying an appropriate measure of association remains a challenge to behavioural ecologists. Here, we use automatically recorded feeder visit data from four bird systems to compare three methods to identify a social association: (1) strict time-window, (2) co-occurrence in a group, and (3) arrival-time. We tested the similarity of the resulting networks by comparing the repeatability and sensitivity of individuals’ social traits (network degree, strength, betweenness). We found that networks constructed using different methods but applying similar, ecologically relevant definitions of associations based on individuals’ spatio-temporal co-occurrence, showed similar characteristics. Our findings suggest that the different methods to construct animal social networks are comparable, but result in subtle differences driven by species biology and feeder design. We urge researchers to carefully evaluate the ecological context of their study systems when making methodological decisions. Specifically, researchers in ecology and evolution should carefully consider the biological relevance of an edge in animal social networks, and the implications of adopting different definitions.

Neodymium isotope composition and rare earth element distribution of East Antarctic continental shelf and deep waters - Alex Griffiths; Myriam Lambelet; Kirsty Crocket; Richard Abell; Barry J. Coles; Katharina Kreissig; David Porter; Frank O. Nitsche; Mark Rehkämper; Tina van de Flierdt (Chemical Geology, 2024)

Geotechnical laboratory testing of lunar simulants and the importance of standardization - V. Santiago Quinteros; Thomas Dylan Mikesell; Luke Griffiths; Alex X. Jerves (Icarus, 2024)

Positive association of SARS-CoV-2 RNA concentrations in wastewater and reported COVID-19 cases in Singapore – A study across three populations - Yvonne Hui Min Wong; Jue Tao Lim; Jane Griffiths; Benjamin Lee; Dzulkhairul Maliki; Janelle Thompson; Michelle Wong; Sae-Rom Chae; Yee Leong Teoh; Zheng Jie Marc Ho; Vernon Lee; Alex R. Cook; et al. (Science of The Total Environment, 2023)

Effects of a mediterranean diet on the gut microbiota and microbial metabolites: A systematic review of randomized controlled trials and observational studies - Rachel Kimble; Phebee Gouinguenet; Ammar Ashor; Christopher Stewart; Kevin Deighton; Jamie Matu; Alex Griffiths; Fiona C. Malcomson; Abraham Joel; David Houghton; Emma Stevenson; Anne Marie Minihane; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Southern South China Sea Dynamics: Sea Level Change from Coupled Model Intercomparison Project Phase 6 (CMIP6) in the 21st Century - Noah Irfan Azran; Hafeez Jeofry; Jing Xiang Chung; Liew Juneng; Syamir Alihan Showkat Ali; Alex Griffiths; Muhammad Zahir Ramli; Effi Helmy Ariffin; Mohd Fuad Miskon; Juliana Mohamed; Kamaruzzaman Yunus; Mohd Fadzil Akhir (Journal of Marine Science and Engineering, 2023)
Sea level rise will significantly impact coastal areas around the world. As a coastal country, Malaysia’s rising sea levels are a significant concern because they would affect 70% of its population. The study of sea level rise is important in order to implement effective mitigation and adaptation strategies. This study investigates the performance of CMIP6 Global Climate Models (GCMs) in simulating sea level rise in the Malaysian seas using various statistical methods. The models’ performances were evaluated by comparing historic CMIP6 GCM runs from 1993 to 2010 with sea level measurements from the satellite altimetry AVISO+ using the Taylor diagram. The SCS (SCSPM and SCSEM) had a higher sea level range and trend in both selected areas than the SM and SS. With 1.5 °C warmings, the multi-model ensemble means predicted that the SCS would rise by 16 mm near the Peninsular, with sea levels increasing by 0.908 m at a rate of 1.5 mm/year, and by 14.5 mm near East Malaysia, with sea levels increasing by 0.895 m at a rate of 1.1 mm/year. In contrast, 2.0 °C warmings project that SCSPM and SCSEM would cause sea levels to rise by 20.2 mm and 21.5 mm, respectively, at a rate of 0.6 mm/year and 0.7 mm/year. This information will provide an insight into Malaysian sea levels between now and the end of the twenty-first century, which will be beneficial for government agencies, academics, and relevant stakeholders.

The effect of rugby training on indirect markers of gut permeability and gut damage in academy level rugby players - Sarah Chantler; Alex Griffiths; Padraic Phibbs; Gregory Roe; Carlos Ramírez-López; Glen Davison; Ben Jones; Kevin Deighton (European Journal of Applied Physiology, 2022)
Purpose To assess indirect markers of intestinal endothelial cell damage and permeability in academy rugby players in response to rugby training at the beginning and end of preseason. Methods Blood and urinary measures (intestinal fatty acid binding protein and lactulose:rhamnose) as measures of gastrointestinal cell damage and permeability were taken at rest and after a standardised collision-based rugby training session in 19 elite male academy rugby players (age: 20 ± 1 years, backs: 89.3 ± 8.4 kg; forwards: 111.8 ± 7.6 kg) at the start of preseason. A subsample ( n = 5) repeated the protocol after six weeks of preseason training. Gastrointestinal symptoms (GIS; range of thirteen standard symptoms), aerobic capacity (30–15 intermittent fitness test), and strength (1 repetition maximum) were also measured. Results Following the rugby training session at the start of preseason, there was an increase (median; interquartile range) in intestinal fatty acid binding protein (2140; 1260–2730 to 3245; 1985–5143 pg/ml, p = 0.003) and lactulose:rhamnose (0.31; 0.26–0.34 to 0.97; 0.82–1.07, p < 0.001). After six weeks of preseason training players physical qualities improved, and the same trends in blood and urinary measures were observed within the subsample. Overall, the frequency and severity of GIS were low and not correlated to markers of endothelial damage. Conclusions Rugby training resulted in increased intestinal endothelial cell damage and permeability compared to rest. A similar magnitude of effect was observed after six weeks of pre-season training. This was not related to the experience of GIS.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Fluid–Structure Interaction Models of Bioprosthetic Heart Valve Dynamics in an Experimental Pulse Duplicator - Jae H. Lee; Alex D. Rygg; Ebrahim M. Kolahdouz; Simone Rossi; Stephen M. Retta; Nandini Duraiswamy; Lawrence N. Scotten; Brent A. Craven; Boyce E. Griffith (Annals of Biomedical Engineering, 2020)
Computer modeling and simulation is a powerful tool for assessing the performance of medical devices such as bioprosthetic heart valves (BHVs) that promises to accelerate device design and regulation. This study describes work to develop dynamic computer models of BHVs in the aortic test section of an experimental pulse-duplicator platform that is used in academia, industry, and regulatory agencies to assess BHV performance. These computational models are based on a hyperelastic finite element extension of the immersed boundary method for fluid–structure interaction (FSI). We focus on porcine tissue and bovine pericardial BHVs, which are commonly used in surgical valve replacement. We compare our numerical simulations to experimental data from two similar pulse duplicators, including a commercial ViVitro system and a custom platform related to the ViVitro pulse duplicator. Excellent agreement is demonstrated between the computational and experimental results for bulk flow rates, pressures, valve open areas, and the timing of valve opening and closure in conditions commonly used to assess BHV performance. In addition, reasonable agreement is demonstrated for quantitative measures of leaflet kinematics under these same conditions. This work represents a step towards the experimental validation of this FSI modeling platform for evaluating BHVs.

Substrate oxidation and the influence of breakfast in normobaric hypoxia and normoxia - Alex Griffiths; Kevin Deighton; Oliver M. Shannon; Jamie Matu; Roderick King; John P. O’Hara (European Journal of Applied Physiology, 2019)

Interpreting environmental change in coastal Alaska using traditional and scientific ecological knowledge - William G. Ambrose; Lisa M. Clough; Jeffrey C. Johnson; Michael Greenacre; David C. Griffith; Michael L. Carroll; Alex Whiting (Frontiers in Marine Science, 2014)

Improving the assessment and valuation of climate change impacts for policy and regulatory analysis - Alex L. Marten; Robert E. Kopp; Kate C. Shouse; Charles W. Griffiths; Elke L. Hodson; Elizabeth Kopits; Bryan K. Mignone; Chris Moore; Steve C. Newbold; Stephanie Waldhoff; Ann Wolverton (Climatic Change, 2013)